2017
DOI: 10.1021/acs.jmedchem.7b00635
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Von Hippel-Lindau-Recruiting Proteolysis Targeting Chimeras (PROTACs) of TANK-Binding Kinase 1

Abstract: Proteolysis targeting chimeras (PROTACs) are bifunctional molecules that recruit an E3 ligase to a target protein to facilitate ubiquitination and subsequent degradation of that protein. While the field of targeted degraders is still relatively young, the potential for this modality to become a differentiated and therapeutic reality is strong, such that both academic and pharmaceutical institutions are now entering this interesting area of research. In this article, we describe a broadly applicable process for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
201
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(207 citation statements)
references
References 29 publications
6
201
0
Order By: Relevance
“…Compound 3i was recently developed as VHL‐based PROTAC targeting another serine/threonine kinase, TANK‐binding kinase 1 (TBK1), which has been implicated in innate immune response, tumorigenesis, and development. Compound 3i can completely knockdown TBK1 in several cancer cell lines at a concentration of 100 nM, indicating the excellent efficiency of this compound (Figure d) . In addition, VHL‐based PROCTACs have been shown to target transmembrane receptor tyrosine kinases (RTKs) as well as mutants of RTKs …”
Section: All‐small‐molecule Protacs: a Potent And Promising Tool To Ementioning
confidence: 95%
See 1 more Smart Citation
“…Compound 3i was recently developed as VHL‐based PROTAC targeting another serine/threonine kinase, TANK‐binding kinase 1 (TBK1), which has been implicated in innate immune response, tumorigenesis, and development. Compound 3i can completely knockdown TBK1 in several cancer cell lines at a concentration of 100 nM, indicating the excellent efficiency of this compound (Figure d) . In addition, VHL‐based PROCTACs have been shown to target transmembrane receptor tyrosine kinases (RTKs) as well as mutants of RTKs …”
Section: All‐small‐molecule Protacs: a Potent And Promising Tool To Ementioning
confidence: 95%
“…Thus, the generation of small‐molecule ligands with high specificity and affinity will remarkably accelerate the development of PROTACs. Second, since PROTACs with different linker lengths exhibit obviously different efficiencies for target degradation, the principles of linker design need to be elucidated. Third, PROTACs with the same ligand for the target protein and different ligands for E3 ubiquitin ligases have variable selectivity for target proteins and efficiencies of target protein degradation .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…[ 136 ] Moreover, SGK3‐PROTAC1, which was constructed by the SGK inhibitor 308R and the VHL ligand VH032, was shown to selectively degrade SGK3 at submicromolar concentrations. [ 137 ] Furthermore, other kinases, such as Bruton's tyrosine kinase, [ 138 ] anaplastic lymphoma kinase, [ 139 ] Fms‐like tyrosine kinase 3, [ 140 ] serine/threonine kinase TANK‐binding kinase 1 (TBK1), [ 141 ] CDK6, [ 142 ] and CDK9, [ 143 ] have been designed as effective PROTACs using kinase inhibitors and E3 ligands such as VHL, CRBN, and MDM2, respectively.…”
Section: Strategies For Selective Protein Degradationmentioning
confidence: 99%
“…Over the past decade, PROTACs have been developed to address an ever-expanding collection of target proteins. Owing to the availability of well-validated chemical matter to repurpose as PROTAC warheads, the majority of early reports focused on degraders of hormone receptors [10][11][12][13], BET-family proteins [14][15][16] and kinases [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. More recently, the applicability of PROTACs has been broadened to include multi-functional proteins (e.g., TRIM24 [34], SMARCA2 [35] tau [36,37]), and HaloTag7-fused proteins for chemical genetics [38].…”
Section: Introductionmentioning
confidence: 99%
“…Our study seeks to do so by modeling the PROTAC's ability to induce formation of the target protein/PROTAC/E3 ligase ternary complex. It has been shown that a PROTAC's ability to bind the target protein is not the primary determinant of whether efficient degradation occurs; rather, it has been suggested that formation of the ternary complex is limiting (i.e., the ability of the PROTAC to simultaneously bind both the target protein and the E3 ligase) [20,22]. It has further been shown that PROTAC selectivity does not necessarily mimic that of its target-binding warhead, but rather depends sensitively on the linker [20,23,24,33]: accordingly, we therefore additionally explore whether the same structure-based modeling can be used to rationalize how and why PROTAC selectivity differs from that of the warhead.…”
Section: Introductionmentioning
confidence: 99%